TcTASV Antigens of Trypanosoma cruzi: Utility for diagnosis and high accuracy as biomarkers of treatment efficacy in pediatric patients - Floridia Yapur, Noelia Aldana del Rosario (2019)
The discovery and characterization of novel parasite antigens to improve the diagnosis of Trypanosoma cruzi by serological methods and for accurate and rapid follow-up of treatment efficiency are still needed. TcTASV is a T. cruzi-specific multigene family, whose products are expressed on the parasite stages present in the vertebrate host. In a previous work, a mix of antigens from subfamilies TcTASV-A and TcTASV-C (Mix A + C) was sensitive and specific to identify dogs with active infection of high epidemiological relevance. Here, TcTASV-A and TcTASV-C were assayed separately as well as together (Mix A + C) in an ELISA format on human samples. The Mix A + C presented moderate sensitivity (78%) but high diagnostic accuracy with a 100% of specificity, evaluated on healthy, leishmaniasic, and Strongyloides stercoralis infected patients. Moreover, antibody levels of pediatric patients showed-2 years posttreatment-diminished reactivity against the Mix A + C (P < 0.0001), pointing TcTASV antigens as promising tools for treatment follow-up.